2016
DOI: 10.1016/j.bbadis.2016.05.015
|View full text |Cite
|
Sign up to set email alerts
|

Nuclear speckles are detention centers for transcripts containing expanded CAG repeats

Abstract: The human genetic disorders caused by CAG repeat expansions in the translated sequences of various genes are called polyglutamine (polyQ) diseases because of the cellular "toxicity" of the mutant proteins. The contribution of mutant transcripts to the pathogenesis of these diseases is supported by several observations obtained from cellular models of these disorders. Here, we show that the common feature of cell lines modeling polyQ diseases is the formation of nuclear CAG RNA foci. We performed qualitative an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
26
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 31 publications
(34 citation statements)
references
References 48 publications
6
26
0
Order By: Relevance
“…7). Consistent with previous studies 29 , we find that the disruption of nuclear speckles with tautomycin also disrupts the 47xCAG RNA foci (Extended Data Fig. 7).…”
Section: Inhibitors Of Rna Gelation Disrupt Focisupporting
confidence: 92%
See 1 more Smart Citation
“…7). Consistent with previous studies 29 , we find that the disruption of nuclear speckles with tautomycin also disrupts the 47xCAG RNA foci (Extended Data Fig. 7).…”
Section: Inhibitors Of Rna Gelation Disrupt Focisupporting
confidence: 92%
“…Similar to the endogenous foci in patient derived fibroblasts 29 , the induced RNA foci co-localized with the SC-35 marker for nuclear speckles (Fig. 3a, Extended Data Fig.…”
Section: Cag Repeat Rnas Phase Separate In Cellsmentioning
confidence: 66%
“…Such diseases include dominantly inherited disorders that are associated with the presence of long repeat expansions in the non-coding or coding regions of individual genes (Figure 4). In this case, the interaction between proteins and mutant RNA often results in the immobilization of these proteins in specific structures that are termed RNA foci, which are the pathogenic hallmarks of this type of disease (136139). The identification of proteins that are bound to CUG repeats in myotonic dystrophy type 1 (DM1) led to the development of the RNA gain-of-function model, which posits that expanded repeats sequester RNA-binding proteins from their normal function (140143).…”
Section: Methods For Identifying Proteins That Bind To Expanded Rna Rmentioning
confidence: 99%
“…According to recent studies, RNA foci are not static, but rather dynamic structures, as shown for CGG and CUG repeats (Querido et al, 2011; Strack et al, 2013), and mutant transcripts were accessible to ON reagents. However, CAG RNA foci differ in morphology and localization from RNA foci found in other repeat expansion diseases (Wojciechowska and Krzyzosiak, 2011; Urbanek et al, 2016). Therefore, despite the successful deconstruction of RNA foci in other repeat expansion diseases (Supplementary Table S1), the ability to decrease CAG RNA foci phenotype was not obvious.…”
Section: Discussionmentioning
confidence: 75%
“…Both RNA and protein products from the mutant allele are proposed to be involved in the pathogenic process; therefore, the most promising therapeutic approaches are designed to target the mutant transcripts. Mutant mRNA is partially or temporarily retained in the nucleus within splicing speckles, as shown in multiple types of cellular models of polyQ diseases (De Mezer et al, 2011; Urbanek et al, 2016). Increased retention of mutant RNA in the nucleus is associated with compromised functions of proteins that bind to mutant RNA (Jazurek et al, 2016); examples of such malfunctions are alternative splicing abnormalities (Mykowska et al, 2011; Sathasivam et al, 2013; Cabrera and Lucas, 2016) and other gene expression alterations (Sharma and Taliyan, 2015).…”
Section: Introductionmentioning
confidence: 99%